Comparison of Antioxidant Activities of Red Pedada (Sonneratia caseolaris L.) Mangrove Forest Area, Jambi Province - Sutra, Inada; Yanti, Selvi Purnama; Alvi, Alvi; Ihsan, Mahya; Wahyuni, Fitra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Red pedada (Sonneratia caseolaris L.) is a mangrove plant that is often found in the East Tanjung Jabung Regency, Jambi Province. This plant contains several secondary metabolite compounds including alkaloids, flavonoids, saponins, polyphenols, tannins, triterpenoids and steroids. This study aims to determine the comparison of antioxidant activity contained in extracts of leaves and fruit of red pedada (Sonneratia caseolaris L.). Extraction was carried out using the maceration method using 96% ethanol solvent. The antioxidant activity test was carried out using the DPPH (diphenyl-picrylhydrazyl) method and measured using a UV-Vis spectrophotometer at a wavelength of 517 nm. The results of the phytochemical test of red pedada leaf and fruit extract (Sonneratia caseolaris L.) showed positive results for alkaloid, flavonoid, saponin, polyphenol and tannin compounds. Meanwhile, steroid compounds were only positive in leaves, and triterpenoids only in fruit. The results of the comparison of the antioxidant activity test of red pedada leaf and fruit extracts (Sonneratia caseolaris L.) showed better antioxidant activity in the leaves based on the IC50 value of 14,196 ppm and in the fruit of 24,590 ppm. The conclusion of this research is that red pedada leaf and fruit extract (Sonneratia caseolaris L.) has antioxidant activity very strong category.